1965
DOI: 10.1172/jci105306
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification and properties of the isoniazid transacetylase in human liver. Its relationship to the acetylation of p-aminosalicylic acid.

Abstract: The heritable trait of rapid and slow inactivation of isoniazid (isonicotinic acid hydrazide) in man is a topic of considerable interest in the developing field of pharmacogenetics (1). Although differences in acetylation appear to be the principal reason for inactivation differences, knowledge of the specific enzymic basis as well as of the relationship of this trait to the acetylation of chemically related compounds is scant.Some in vitro information has been obtained. Localization of the variability in acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

1969
1969
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(35 citation statements)
references
References 21 publications
3
32
0
Order By: Relevance
“…The rate of activity of this enzyme is genetically determined and populations may be divided into 'slow' and 'fast' acetylators with implications for the dosage requirements of a variety of drugs [2]. The total N-acetyltransferase activity present in the liver of a rapid acetylator is at least twice as high as that found in a slow acetylator [3] and there is considerable racial variation with most Caucasoid populations having approximately 50% of their number in each group [2]. Slow acetylators are more prone than fast acetylators to develop peripheral neuropathy when treated with isoniazid [4,5] and a study from Finland found that seven out of nine Type I (insulin-dependent) diabetic children were fast acetylators [6].…”
mentioning
confidence: 99%
“…The rate of activity of this enzyme is genetically determined and populations may be divided into 'slow' and 'fast' acetylators with implications for the dosage requirements of a variety of drugs [2]. The total N-acetyltransferase activity present in the liver of a rapid acetylator is at least twice as high as that found in a slow acetylator [3] and there is considerable racial variation with most Caucasoid populations having approximately 50% of their number in each group [2]. Slow acetylators are more prone than fast acetylators to develop peripheral neuropathy when treated with isoniazid [4,5] and a study from Finland found that seven out of nine Type I (insulin-dependent) diabetic children were fast acetylators [6].…”
mentioning
confidence: 99%
“…In 1965, Jenne [24] suggested that acetylation of monomorphic and polymorphic substrates was mediated by separate enzymes, a prediction confirmed almost 25 years later when the cloning of the human NAT1 and NAT2 genes was achieved [25] and functional characterization of their expressed products and those present in human liver was studied [26]. It is now clear that human NAT1 and NAT2 are independently expressed proteins and that NAT2 possesses catalytic specificity for those substrates whose rates of acetylation show polymorphic variation correlating with that of isoniazid [26,27].…”
Section: Biochemical Studiesmentioning
confidence: 99%
“…These substrates are called monomorphic, in contrast to the polymorphic substrates isoniazid, procainamide, and others. Jenne et al (9), during the first detailed biochemical studies of drug acetylation in man, proposed that two different N-acetyltransferase enzymes were responsible for the metabolism of monomorphic and polymorphic arylamines. Moreover, it appeared that the observed genetic variation in acetylation of polymorphic substrates was related to differences in the quantity of one of these enzymes present in human liver cytosol, rather than to altered kinetic characteristics of a structural variant.…”
Section: The Molecular Mechanism Ofthe Acetylation Polymorphismmentioning
confidence: 99%